KNOWLEDGE, ATTITUDE, AND PERCEPTION OF PEOPLE IN COMPLIANCE WITH THE COVID-19 HEALTH PROTOCOL - Septa Ria Agina Perangin Angin; Erni Astutik (Jurnal Berkala Epidemiologi, 2022)
Background: The COVID-19 pandemic has infected many people and impacted the political, economic, social, cultural, defence, security aspects, and welfare of society. One of the regions of Indonesia with the most cases is East Java Province which has reached more than 46,984 confirmed cases. Purpose: This study aimed to analyze self-awareness and the amount of risk in terms of knowledge, attitudes, and perceptions of the people of East Java Province with compliance with the COVID-19 health protocol after the adaptation of new habits. Methods: This study used a cross-sectional study design. This study was conducted with inclusion criteria in people who live in East Java Province, have a productive age of female (15-49 years) and male (15-59 years), and are willing to be respondents in the study. Exactly 285 respondents participated in the study. This study measure demographics, knowledge, attitude, perception, and practice of health protocols variables. We used a questionnaire to collect data via a google form. The data were analyzed using the Chi-square test. Results: The results showed that there was a relationship between attitudes and perceptions about COVID-19 on compliance with the COVID-19 Health protocol (p-value = 0.01), and there was no relationship between knowledge (p-value = 0.58), age (p-value = 0.66), sex (p-value = 0.61), and education (p-value = 0.23) with compliance with the COVID-19 Health protocol. Conclusion: Respondents' compliance with the COVID-19 health protocol is still low. Community education efforts are needed to implement health protocols.